Impact of comorbidities on older patients undergoing open heart surgery. Issue 5 (10th January 2022) - Mikus, Elisa; Calvi, Simone; Albertini, Alberto; Tripodi, Alberto; Zucchetta, Fabio; Brega, Carlotta; Pin, Maurizio; Cimaglia, Paolo; Ferrari, Roberto; Campo, Gianluca; Serenelli, Matteo
Abstract : Background: The number of elderly patients undergoing cardiac surgery is increasing. Age greater than 80 years has been identified as a strong independent risk factor for shortand long-term survival. The current study is aimed to identify the impact of preoperative comorbidities on early and late outcomes in older patients undergoing cardiac surgery. Methods: Baseline characteristics, procedurals and postoperative complications of all patients undergoing cardiac surgery at our institution are collected. The current analysis is focused on patients aged at least 80 years at the time of intervention and treated from January 2010 to December 2019. Results: In-hospital mortality resulted as 6.3%. Redo intervention [odds ratio (OR) 2.49, 95% confidence interval (CI) 1.13–5.48], chronic obstructive pulmonary disease (COPD) (OR 2.99, 95% CI 1.75–5.12) and peripheral arterial disease (PAD) (OR 2.23, 95% CI 1.30–3.81) were independent baseline predictors of outcome in the multivariate analysis. Prolonged extracorporeal circulation time, need for transfusion and prolonged intubation time strongly and independently predicted in-hospital mortality. During a mean follow-up of 3.6 years 34.3% of patients died and unplanned admission (HR 1.33, 95% CI 1.05–1.67), NYHA class III-IV (HR 1.35, 95% CI 1.12–1.64), diabetes (HR 1.27, 95% CI 1.01–1.59), COPD (HR 1.60, 95% CI 1.25–2.04) and PAD (HR 1.32, 95% CI 1.03–1.71) resulted as independent predictors of all-cause death. Conclusion: Cardiac surgery is feasible in octogenarians, with an acceptable risk of mortality. Chronological age itself should not be the main determinant of choice while referring patients for cardiac surgical intervention. Comorbidities such as COPD, PAD and diabetes need to be taken into account for risk stratification.